Smokeless tobacco: knowledge, attitudes and usage in Pakistan - Hammad Atif Irshad; Sajjan Raja; Hamzah Jehanzeb; Wamiq Ali Shaikh; Umair Saleem; Shahzil Abdur Rehman Malik; Akmal Shahzad; Mamoon Shaikh; Nousheen Iqbal; Javaid Ahmed Khan (Journal of Health, Population and Nutrition)
Abstract Background Smokeless tobacco (SLT) encompasses products that are not burnt but instead consumed orally or nasally. One-third of tobacco is consumed in the smokeless form in South Asia. Despite its widespread usage, there has been limited empirical research on the prevalence and factors influencing SLT consumption in Pakistan. This study aimed to provide an assessment of SLT knowledge, attitudes, and usage in Pakistan. Methods Using an online questionnaire, a cross-sectional survey was conducted across Pakistan. Convenience sampling was used to disseminate, and expert approval was sought followed by a pilot study to validate the questionnaire. A comprehensive questionnaire was developed using elements from the Global Adult Tobacco Survey and other tools which had previously been utilized within Pakistan. Participants’ responses were described using descriptive statistics, and SPSS version 26 was used to perform linear and logistic regression. A p-value of less than 0.05 was considered statistically significant. Results Data was collected from 1,195 participants among which 85.86% of participants had heard of SLTs prior to the survey. Sex, province, household income and previous doctor visits were significant determinants to product knowledge through which 72.55% agreed that these products can lead to serious illnesses but 30% noted a lack of knowledge on legality. General attitudes agreed that it makes one feel unwell (44.1%), gives a sense of guilt (43.85%) and more research is needed on it (54.39%). Negative health effects were the biggest deterrent from pursuing these products for 60.33% of participants. Among significant factors influencing the use of SLTs, the greatest odds of use were found with use as an alternative to cigarettes (OR 4.45) and secondly, due to its availability in a liked flavor (OR 2.27). About 31% reported to have used the product once, with 69.82% of current users expressing a desire to quit. Conclusions Although adequate knowledge and aligning attitudes exist for SLTs, light is shed in the face of a sustaining public health problem. We offer important insights that can guide the creation of focused interventions meant to lower SLT use, and the health hazards associated with it in the Pakistani community by highlighting important myths, incentives, and deterrents.